2013
DOI: 10.3341/kjo.2013.27.2.98
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Morphology of Diabetic Macular Edema and Renal Dysfunction in Diabetes

Abstract: PurposeTo determine the correlation between renal dysfunction and the morphologic changes of macular edema in diabetes.MethodsThe current study included 93 patients with diabetic macular edema based on optical coherence tomography (OCT) who completed systemic condition testing one month before or after the OCT. Based on the OCT findings, patients were divided into the following five groups: group A (diffuse), group B (cystoid), group C (serous), group D (vitreomacular tractional), and group E (a mixed presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 6 publications
0
18
0
1
Order By: Relevance
“…Very few studies have been conducted to determine the correlation of non-ocular factors such as CKD secondary to diabetes with various morphological patterns of DME seen on OCT. [12,20,21] Also the previous studies conducted were single centre studies with a relatively small sample size. None of the studies performed have demonstrated the impact of CKD on the recently described visual prognostic biomarkers in DME and correlated them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Very few studies have been conducted to determine the correlation of non-ocular factors such as CKD secondary to diabetes with various morphological patterns of DME seen on OCT. [12,20,21] Also the previous studies conducted were single centre studies with a relatively small sample size. None of the studies performed have demonstrated the impact of CKD on the recently described visual prognostic biomarkers in DME and correlated them.…”
Section: Discussionmentioning
confidence: 99%
“…On review of literature several studies have used proteinuria as a marker of nephropathy and found a relation between disease severity and proteinuria. [12,21,22] However an inconsistent relation has been reported between the two and therefore in our study we have used eGFR as a marker of nephropathy which is possibly a better marker for nephropathy as ethnic variations and age of the patient are used for its determination. Also, eGFR is possibly the earliest marker for nephropathy and albuminuria is an inconsistent marker that may regress or progress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Los resultados de este estudio aplican para pacientes con EMCS focal; en el edema difuso, que generalmente tiene un engrosamiento y cierre capilar extenso 21 , los fármacos antiangiogénicos intravítreos han remplazado a la fotocoagulación. Además, el edema macular difuso se asocia con condiciones sistémicas como dislipidemia y nefropatía diabética, lo cual podría aumentar la proporción de ojos con edema recurrente 22 ; estas variables tienen una menor contribución en el edema macular focal, en el que la filtración viene de uno o más sitios de daño localizados en la red capilar 23 .…”
Section: Discussionunclassified